2013
DOI: 10.1039/c2dt31718d
|View full text |Cite
|
Sign up to set email alerts
|

Hydration of the calcium(ii) ion in an aqueous solution of common anions (ClO4−, Cl−, Br−, and NO3−)

Abstract: Raman spectra of aqueous calcium salt solutions, Ca(ClO(4))(2), CaCl(2), CaBr(2), and Ca(NO(3))(2), were measured from the concentrated solution stage to more dilute solutions (6.08-0.1 mol L(-1)) at 23 °C in water and heavy water down to 40 cm(-1). In aqueous Ca(ClO(4))(2) solutions a strongly polarized band at 283 cm(-1) (full width at half height (fwhh) = 68 cm(-1)) was observed. The mode at 283 cm(-1) was assigned to the Ca-O symmetric stretching vibration of the hexa-aqua Ca(2+) ion, [Ca(OH(2))(6)](2+), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
92
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(100 citation statements)
references
References 83 publications
8
92
0
Order By: Relevance
“…Here, x is the number of Cl -, W is the abbreviation of water molecule, n denotes the total number of water molecules, mL indicates the total coordination number of Ca 2+ . The B3LYP/aVDZ calculations show that [CaCl x ] 2−x hydrates prefer six-coordinated structures, which agrees with the results of Rudolph et al17 . As observed from…”
supporting
confidence: 83%
See 1 more Smart Citation
“…Here, x is the number of Cl -, W is the abbreviation of water molecule, n denotes the total number of water molecules, mL indicates the total coordination number of Ca 2+ . The B3LYP/aVDZ calculations show that [CaCl x ] 2−x hydrates prefer six-coordinated structures, which agrees with the results of Rudolph et al17 . As observed from…”
supporting
confidence: 83%
“…1-4 Inorganic CaCl 2 salt plays vital roles in many biochemical processes 1,2 and is a major component of the geothermal brines [5][6][7] and energy storage materials. [8][9][10] This great importance has prompted numerous studies on CaCl 2 aqueous solutions, both experimentally [11][12][13][14][15][16][17][18][19][20] and theoretically, [15][16][17][18][19][20][21][22][23] in recent decades. In the published works, ion-associated characteristics in CaCl 2 aqueous solutions, in particular contact ion pair (CIP) which was firstly proposed by Phutela and Pitzer 11 to explain an anomaly in the thermodynamic behavior in near 5.0 mol·kg -1 CaCl 2 aqueous solutions, were generally suspected.…”
Section: Introductionmentioning
confidence: 99%
“…Geometries CIP structures in work of Phutela and Pitzer [16], whereas the existence of CIP or SSIP/s structures was frequently doubted in early studies, especially in some CPMD results and experiment work [17][18][19][20][21][22]. Since the constraint of Ca 2 + on the second hydration shell cannot be neglected, as pointed out by the work of Bai et al [8], the stabilities of CIP and SSIP conformers in aqueous solution should be investigated when the perturbation of bulk water or outer hydration shells on these ion associated species has been properly considered.…”
Section: Structural Parameters a Energy Parameters Bmentioning
confidence: 99%
“…Phutela and Pitzer suggested the formation of contact ion pair (CIP) in CaCl 2 aqueous solution, compared to the MgCl 2 aqueous solution [16]. However, in early works, the formation of CIP conformer in CaCl 2 aqueous solution was generally suspected both in some MD simulations and experimental investigations [17][18][19][20][21][22]. Recently, combined with X-ray absorption fine structure spectral and an X-ray diffraction spectral analyses, the work of Pham and Fulton demonstrated the presence of CIP and solvent-shared ion pair (SSIP) 2 Q.…”
Section: Introductionmentioning
confidence: 98%
“…5 The O-atoms of the three waters in the equatorial plane (capping position) are separated from the cation by a bond distance of 2.64Å, while six water molecules at the vertices of the trigonal prism have a La-O bond distance of 2.515Å. 5,6 A recent Raman spectroscopic investigation revealed that in concentrated La(ClO 4 ) 3 (aq) ion pairs are formed while in dilute solutions the undisturbed [La(H 2 O) 9 ] 3+ species exist.…”
Section: Introductionmentioning
confidence: 99%